The Importance of Supplementation in Vegan and Vegetarian Diets for Adults - Wójtowicz, Justyna; Sajkiewicz, Ilona; Rudnicka, Katarzyna; Miga-Orczykowska, Nadia; Lemieszek, Paulina; Jasiuk, Ilona; Pustelniak, Martyna; Krukar, Katarzyna; Łukaszewska, Ewa; Kister, Klaudia (Journal of Education, Health and Sport, 2024)
Introduction and purpose Vegan and vegetarian diets are popular due to health, ethical, and ecological benefits, but they risk nutrient deficiencies. This article reviews research on supplementation to meet the nutritional needs of adults on these diets. It provides recommendations for different life stages, including pregnancy, aging, and physical activity, and highlights the risks of excessive or inadequate supplementation, stressing the need for personalized dietary approaches.. Material and method A systematic review of the past decade's literature focused on peer-reviewed articles from databases like PubMed, Google Scholar, and Scopus. It included studies on adults adhering to vegan or vegetarian diets, evaluating supplementation's effects on nutrition and health. The review encompassed observational studies, interventions, meta-analyses, and systematic reviews, using keywords such as "vegan diet," "vegetarian diet," "supplementation," "nutrient deficiencies," and "adult health." State of knowledge Research shows that well-planned vegan or vegetarian diets can be healthy for adults, but often need supplementation to prevent nutrient deficiencies. Clinical studies confirm the efficacy of supplements. Specific groups, like pregnant and lactating women and those with regular physical activity, may need extra vitamins and minerals. Excessive supplementation poses health risks, so a personalized approach considering individual needs, health status, age, and lifestyle is crucial. Conclusions A well-balanced vegan or vegetarian diet, supported by appropriate supplementation, can be beneficial for the health of adults. A personalized approach to supplementation is essential, taking into account specific nutritional needs, pregnancy, health status, age, and lifestyle. Regular monitoring of nutritional status and adjusting supplementation to the body's current needs is crucial for maintaining optimal health.